La rebelión de Huánuco en 1812 y la investigación histórica del siglo XXI - Bazán Díaz, Marissa (2018)
The present work will seek to identify the historiographic analysis carried out by the researchers about the Huanuco rebellion in 1812, in the middle of the crisis of the Spanish monarchy and the installation of Cadiz Cortes, a period of abuses of the peninsular authorities against the population —by prohibiting them from exporting agricultural products and selling tobacco— which would have provoked discontent, uprising and the installation of a board in the area. The objective of this paper is to recognize those proposals on the causes, consequences, actors and the impact that the scholars have identified in this rebellion that go beyond the economic matter; especially what it is for the participation of the population of the common to manage to cover those gaps that could arise in the light of the new historical political perspective.